Volleyball Players' Performance During Competition and Its Relation to The Coach's Familiarity with The Pedagogical Requirements of Training - Khalid, Almaryami; Baaziz, Mohamed; Khalfoun, Jihen; Abderrahman, Abderraouf Ben (Advances in Social Sciences Research Journal, 2024)
The study outlines the necessary training requirements for a coach to achieve athletic excellence in players. These factors include the coach's scientific knowledge, such as their understanding of scientific concepts related to modern coaching and assessment methods, knowledge of fundamentals and training methods, ability to instill personal qualities in players, and knowledge of teaching and learning methods. Additionally, the coach's personal qualities in relation to the players are important, including their behavior, ability to develop a spirit of competition, socialization, and team spirit, and understanding of the educational aspects of coaching. Finally, the coach's application of scientific knowledge in training is crucial, including mastery of the training load, game plans, and the organizational aspects of matches. Furthermore, the coach's understanding of the selection criteria is recognized as a crucial element in enhancing player performance.